Reconstruction of continental mean air temperature across the PETM of IODP Hole 302-M0004A (Appendix A) - Johan W H Weijers; Stefan Schouten; Appy Sluijs; Henk Brinkhuis; Jaap S Sinninghe Damsté (PANGAEA, 2007)
The Palaeocene-Eocene Thermal Maximum (PETM; ~55.5 Ma) is a geologically relatively brief episode of extreme warmth. Both deep and surface ocean temperatures increased by up to 5 °C in equatorial waters and up to 8 °C in mid and high latitude waters. From the continents, the annual mean air temperature response during the PETM is still largely unknown, mainly due to a lack of quantitative temperature proxies and sufficient suitable, continuous high resolution records. Recently, a new proxy for continental temperature reconstructions has been proposed, based on the distribution of membrane lipids of bacteria in present-day soils [Weijers et al., 2007, doi:10.1016/j.gca.2006.10.003] and shown to reconstruct annual mean air temperature. In this study we applied this new proxy in an attempt to reconstruct the air temperature in high latitude continental areas during the PETM by analysis of a marine sedimentary sequence obtained from the Lomonosov Ridge in the central Arctic Ocean (Integrated Ocean Drilling Program Expedition 302, Site 004, Hole A). The results indicate a warming of ~8 °C above background values of ~17 °C. This warming is coincident with a similar rise in sea surface temperatures documented earlier. Our results thus further confirm the warm conditions in the Arctic, and point to a strongly reduced latitudinal temperature gradient during the PETM.
Supplement to: Weijers, JWH et al. (2007): Warm arctic continents during the Palaeocene-Eocene thermal maximum. Earth and Planetary Science Letters, 261(1-2), 230-238, https://doi.org/10.1016/j.epsl.2007.06.033